Structure study of donor doped barium titan ate prepared from citrate solutions - Stojanović B.D.; Mastelaro V.R.; Paiva Santos C.O.; Varela J.A. (Science of Sintering, 2004)
Barium titanates doped with Nb5+, and Y3+, were prepared. The starting powders were synthesized from citrate solutions by the Pechini process and partial Pechini process in two steps. Sintering was performed in the range from 13100 up to 13800C for 2 hours in air atmosphere. The structural study concerning the incorporation of Nb and Y ions in the barium titan ate crystal lattice was performed by XRD, XANES and EXAFS techniques. The dielectric properties were analyzed and the relationship between properties and structure of doped barium titan ate was established.